THE ROLE OF GOVERNMENT IN THE DEVELOPMENT OF COASTAL COMMUNITY IN MAKASSAR CITY - Umar Nain (Sosiohumaniora, 2022)
This study aims to analyze the role of government in the development of coastal communities in the city of Makassar. The research design used is a qualitative descriptive method with an inductive approach. The data sources in this study are the management of each institution, empowered community members, government officials of Makassar city, and the Non-Government Organizations who implement activities in coastal communities. Data collection was conducted through questionnaires, in depth interviews, and documentation. Data analysis techniques used are qualitative data analysis and comparative case study. The results showed that economic development could be felt by traders and economic actors around the reclamation area, while shellfish-seeking fishing communities are experiencing difficulties because of reclamation. The institutional role in the development of tourism in the city of Makassar is still dominated by government agencies; the role is continually active, especially in programs and policies, while implementing many conducted by private parties. The development of marine tourism in coastal areas and small islands is one of the latest approaches to coastal communities. This is a manifestation of the community’s desire to maintain the existence of coastal and marine natural resources for the fulfillment of their needs to be utilized sustainably.